1976
DOI: 10.1037/h0088039
|View full text |Cite
|
Sign up to set email alerts
|

Role of thyroid hormones in an abnormal grooming behavior in thyroidectomized cats and cats with pontile lesions.

Abstract: Thyroidectomized cats and cats with pontile lesions exhibit the same abnormal grooming behavior. Investigations were conducted to determine whether the abnormal grooming behavior in cats with pontile lesions was attributable to a hypothyroid condition. Administration of thyroid hormones abolished the abnormal behavior of thyroidectomized cats but was without effect in cats with pontile lesions. Studies of brain and blood levels of thyroid hormones in cats with pontile lesions failed to detect any differences f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

1976
1976
2003
2003

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Several studies have reported degeneration of the adrenal cortex in hypothyroid animals (e.g., Johansson & Jonsson, 1966), and significant decreases in the size of the zona fasciculata, which secretes glucocorticoids, have been found in hypothyroid animals (Johansson & Jonsson, 1971). Measurements of 11-hydroxycorticoids in our thyroidectomized cats indicate a significant decrease (Randall et al, 1976). Thus, thyroidectomy induces one of the deficits that is essential for the induction of the abnormal grooming behavior.…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…Several studies have reported degeneration of the adrenal cortex in hypothyroid animals (e.g., Johansson & Jonsson, 1966), and significant decreases in the size of the zona fasciculata, which secretes glucocorticoids, have been found in hypothyroid animals (Johansson & Jonsson, 1971). Measurements of 11-hydroxycorticoids in our thyroidectomized cats indicate a significant decrease (Randall et al, 1976). Thus, thyroidectomy induces one of the deficits that is essential for the induction of the abnormal grooming behavior.…”
Section: Discussionmentioning
confidence: 63%
“…The fact that PCPA administration induces grooming fragments in cats with pontile or frontal neocortical lesions (Trulson, 1976b;Trulson & Randall, 1973) and in thyroidectomized cats (Table 1) is further evidence for a similar mechanism. In addition, the superior colliculi are implicated in all three groups, and identical seasonal patterns of change in the areal extent of the grooming fragments occur in each group of cats (Randall & Parsons, 1972;Randall et al, 1976;Trulson, 1976b). Variations in levels of serotonin may be responsible for the seasonal variation in the abnormal behavior.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations